OCA optical pressure-sensitive adhesive with high resilience and high elongation at break and preparation method of OCA optical pressure-sensitive adhesive

By using reversible addition break chain transfer emulsion polymerization technology in OCA optical pressure sensitive glue, the problem of insufficient elasticity and elongation of break of OCA optical glue is solved, and high elasticity and high break elongation are achieved Long rate improves the performance and life of display devices.

CN119432275APending Publication Date: 2025-02-14HANGZHOU ENTRON MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311864024.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

OCA optical pressure-sensitive adhesives have shortcomings in terms of elasticity and elongation of break, resulting in a degradation of performance under high tensile levels, affecting the visual effect and life of the display.

Method used

The pentab copolymer is prepared by a controllable design of reversible addition fracture chain transfer emulsion polymerization. By precisely controlling the type and proportion of monomers, the elasticity and elongation of breaking of OCA optical glue are improved.

Benefits of technology

The high elasticity and high elongation of break of OCA optical glue are achieved, ensuring that it maintains its performance under high tensile level, and improving the quality and life of the display equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432275A_ABST
    Figure CN119432275A_ABST
Patent Text Reader

Abstract

The invention discloses an OCA optical pressure-sensitive adhesive with high resilience and high elongation at break and a preparation method of the OCA optical pressure-sensitive adhesive. The pressure-sensitive adhesive comprises 70-100% of a five-block copolymer, 0-20% of tackifying resin and 0-10% of an antioxidant, the structural general formula of the five-block copolymer is M1-b-M2-b-M3-b-M4-b-M5, M1, M3 and M5 are selected from hard monomers or a mixture of the hard monomers and functional monomers, and the total mass of the five-block copolymer accounts for 30% or below of comonomers; m2 and M4 are selected from soft monomers or a mixture of soft monomers and functional monomers, and the total mass of M2 and M4 accounts for 70% or above of the comonomer. By designing the five-block copolymer, accurate molecular structure regulation and control can be realized, so that high resilience of the OCA optical cement is realized. Due to the coupling effect between molecular chains of the five-block copolymer, the elongation at break of the OCA can be further improved, and it is guaranteed that the OCA still maintains the performance and has high resilience under the high stretching degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to an OCA optical pressure-sensitive adhesive with high resilience and high elongation at break and a preparation method thereof. Background Art

[0002] Optical pressure-sensitive adhesive (OCA) plays a key role in modern optical display technology, such as liquid crystal displays, OLED screens, and touch screens. Among them, highly resilient OCA is extremely important for the visual presentation of display screens. For folding screen devices, when the rebound rate of the optical adhesive is too low or cannot reach close to 100%, it will cause buckling and other behaviors, forming creases visually. In order to meet the needs of high-quality display devices, a highly resilient OCA optical pressure-sensitive adhesive with high resilience and performance stability is required.

[0003] Then, optical adhesives with high resilience are generally composed of UV optical adhesives with high crosslinking degree, and the crosslinking degree is often increased by adding crosslinking agents, photoinitiators or increasing UV light intensity and time. For example, CN 108977160A discloses a photocurable adhesive composition, comprising: component A: 30-70 parts by weight of one or more polyurethane (meth) acrylate polymers; component B: 15-50 parts by weight of one or more monofunctional acrylate monomers, including at least one soft monomer with a glass transition temperature below 20°C; component C: 2-20 parts by weight of one or more hydroxyl-containing functional (meth) acrylate monomers; component D: 0.02-1.0 parts by weight of a defoamer; E: 0.3-5 parts by weight of two or more cleavage-type photoinitiators; and F: 0.10-3.0 parts by weight of an antioxidant. One or more difunctional or trifunctional acrylate monomers can be added to the composition as a crosslinking agent, plasticizer, or silane coupling agent to improve the peeling force and adhesion of the glue, and can be used for the preparation of UV semi-cured (secondary cured) optical films.

[0004] However, this method often results in a significant increase in modulus and a decrease in elongation at break, which may lead to insufficient resilience and aging problems in some applications. With environmental changes and long-term use, OCA may deform and degrade in performance, affecting the performance of the display.

[0005] The triblock copolymer prepared by the fragmentation addition chain transfer emulsion polymerization in CN115260921A has begun to be applied to the field of optical adhesives, which solves the problem of greatly increasing the modulus due to increasing the degree of crosslinking and has a good application scenario. However, it is limited by the characteristics of the triblock structure. During the stretching process, the chain is easily pulled out, resulting in low elongation at break, and breaking at a high degree of stretching, and unable to rebound.

[0006] In order to further enhance its influence and produce better products, a new design is urgently needed to meet high-end application scenarios. Summary of the invention

[0007] The invention aims at the problems of low resilience and elongation at break of OCA pressure-sensitive adhesives, and provides an OCA optical pressure-sensitive adhesive with high resilience and high elongation at break. The five-block copolymer is prepared by controllable design of reversible addition-fragmentation chain transfer emulsion polymerization. Due to the selection of monomers and the chain entanglement between polymers, the five-block copolymer has obvious improvement in resilience and elongation at break compared with the three-block copolymer.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] An OCA optical pressure-sensitive adhesive with high resilience and high elongation at break, comprising 70-100% of a five-block copolymer, 0-20% of a tackifying resin and 0-10% of an antioxidant, based on 100% of the total mass;

[0010] The general structural formula of the five-block copolymer is M1-b-M2-b-M3-b-M4-b-M5, wherein M1, M2, M3, M4, and M5 are comonomers in the block copolymer, wherein M1, M3, and M5 are selected from hard monomers or a mixture of hard monomers and functional monomers, and their total mass accounts for less than 30% of the comonomers; M2 and M4 are selected from soft monomers or a mixture of soft monomers and functional monomers, and their total mass accounts for more than 70% of the comonomers.

[0011] In the present invention, by designing a pentablock copolymer, precise molecular structure regulation can be achieved, thereby achieving high resilience of the OCA optical adhesive. The coupling effect between the molecular chains of the pentablock copolymer can further improve the elongation at break of the OCA optical adhesive, ensuring that it still maintains performance and has high resilience under high stretching. The mechanism of action is as follows Figure 1 Shown and Figure 2 As shown, compared with the blend of multiple triblock or tetrablock copolymers, the five-block copolymer mixture has a higher entanglement force. When it is subjected to mechanical stretching, the chains are more tightly entangled. On the other hand, due to the styrene phase formed by microphase separation, there are three hard segments in a polymer chain, compared with only two hard segments in triblock or tetrablock copolymers, the chain is less likely to be pulled out during stretching.

[0012] This new copolymer provides excellent high resilience and high elongation at break without sacrificing optical clarity and adhesion properties.

[0013] The number average molecular weight of the five-block copolymer is 500,000 to 4,000,000 g / mol; the number average molecular weight of the blocks formed by M1, M3, and M5 is 0.5 to 40,000 g / mol; the number average molecular weight of the blocks formed by M2 and M4 is 50,000 to 500,000 g / mol. When the molecular weight of the hard segment is too high, the material will be too hard, resulting in a very low elongation at break; when the molecular weight of the hard segment is too low, the cohesion of the material will deteriorate, resulting in a decrease in the rebound rate.

[0014] The hard monomer includes one or more of styrene, methyl acrylate, isobornyl acrylate, cyclohexyl acrylate, methyl methacrylate, acrylamide, acrylonitrile and vinyl acetate, and the glass transition temperature thereof is in the range of 60 to 150° C.;

[0015] The soft monomer comprises one or more of ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, octyl acrylate, 2-propylheptyl acrylate, isononyl acrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isooctyl methacrylate, butadiene, isoprene, ethylene-butene and methacrylic acid, and the glass transition temperature ranges from -90 to -30°C;

[0016] The functional monomers include one or more of methacrylic acid, acrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylenedimethylamine methacrylate, methacrylic acid amine, N-hydroxymethyl acrylamide, glycidyl methacrylate and maleic anhydride.

[0017] Preferably, the hard monomer is any one or more of styrene, methyl acrylate, and isobornyl acrylate. The optical adhesive prepared therefrom is colorless and transparent, and has good resilience.

[0018] Preferably, the soft monomer is one or more of isooctyl acrylate, methyl acrylate, 2-propylheptyl acrylate, and isononyl acrylate, which have a lower glass transition temperature, and the prepared optical adhesive material is softer and has a lower modulus.

[0019] Preferably, the functional monomer is acrylic acid and / or itaconic acid, which contain carboxyl groups and can increase the cohesive force and peel strength of the optical adhesive.

[0020] Preferably, the mass of each of M1, M2, M3, M4, and M5 is 1-10%, 30%-60%, 1-10%, 30-60%, and 1-10% of the total monomer mass, respectively, the total monomer mass is 100%, and M2+M4 is above 70%. When the molecular weight of the hard segment is too high, the material will be too hard, resulting in a very low elongation at break of the material; when the molecular weight of the hard segment is too low, the cohesion of the material will deteriorate, resulting in a decrease in the rebound rate.

[0021] Preferably, when M1, M3, and M5 are selected from a mixture of hard monomers and functional monomers, the functional monomers account for 0-15% of the total monomer mass, preferably 2-15%; the functional monomers are added to enhance the cohesion of the optical adhesive and increase the peel strength of the optical adhesive.

[0022] When M2 and M4 are selected from a mixture of soft monomers and functional monomers, the functional monomers account for 0-30% of the total monomer mass, preferably 2-30%; the functional monomers are added to enhance the cohesive force of the optical adhesive and increase the peel strength of the optical adhesive.

[0023] The tackifying resin includes one or more of T-801, T-801L, 900L, 901L, TP2019 and 803L;

[0024] The antioxidant includes any one or more of dialkyl phosphite, triisooctyl phosphite, thiophosphoryl disulfide, antioxidant 1010, antioxidant 168, IRGANOX 1726, IRGANOX 1010, and IRGANOX 1076 of BASF of Germany;

[0025] The dispersion medium includes any one or more of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, methyl ethyl ketone, ethyl acetate and methyl propionate.

[0026] The present invention also provides a method for preparing the OCA optical pressure-sensitive adhesive with high resilience and high elongation at break, comprising the steps of:

[0027] Step 1, dissolving the RAFT agent in water, adding the M1 monomer and mixing, then adding the first initiator, and reacting for 1-3 hours to obtain a latex formed by the M1 homopolymer;

[0028] Step 2, adding sodium hydroxide aqueous solution to the latex of step 1, then adding M2 monomer, water and the second initiator, reacting for 2-15 hours in an anaerobic environment to obtain a M1-b-M2 diblock copolymer emulsion; then sequentially adding M3 monomer, M4 monomer and M5 monomer, adding the second initiator after each addition of new monomers, reacting for 2-15 hours in an anaerobic environment to obtain a M1-b-M2-b-M3-b-M4-b-M5 pentablock copolymer emulsion;

[0029] Step 3, mixing the pentablock copolymer emulsion with a demulsifier, washing and drying the precipitated product to obtain the pentablock copolymer;

[0030] Step 4, dissolving the pentablock copolymer, tackifying resin and antioxidant in a dispersion medium, coating to form a film in an inert gas environment, and drying to obtain the OCA optical pressure-sensitive adhesive.

[0031] The present invention adopts the method of preparing high resilience OCA optical pressure-sensitive adhesive by reversible addition fragmentation chain transfer (RAFT) emulsion polymerization technology, which can accurately control the types and proportions of different segments and achieve more precise polymer performance regulation. The block copolymer prepared by this method has a high molecular weight and can support the preparation of high molecular weight pentablock copolymers.

[0032] The reaction temperature in step 1 is 40-90°C; the reaction temperature in step 2 is 30-60°C; the demulsification temperature in step 3 is 30-60°C; and the demulsification time is more than 0.1h. Compared with the prior art, the reaction temperature is lower, the molecular weight distribution of the synthesized polymer chain is lower, and the regulation of polymer properties is better.

[0033] The chemical structural formula of the RAFT agent is: R-(Mn1-b-Nn2)-X; wherein R is an isopropanoic acid group, an acetic acid group, a 2-cyanoacetic acid group or a 2-aminoacetic acid group; in Mn1, M is a methacrylic acid monomer or an acrylic acid monomer unit, n1 is an average degree of polymerization of M, and the range of n1 is 10 to 30; in Nn2, N is a styrene monomer, a n-butyl acrylate monomer, a methyl acrylate, an isooctyl acrylate or a methyl methacrylate monomer unit, n2 is an average degree of polymerization of N, and the range of n2 is 1 to 8; the X group is an alkyl dithioester group or an alkyl trithioester group, and the added mass of the RAFT agent is 0.2%-1.0% of the total mass of all monomers.

[0034] The demulsifier includes any one or more of a strong acid reagent such as HCl solution, H2SO4 solution, HNO3 solution, HBr solution, and a weak acid reagent such as acetic acid, lactic acid, formic acid, acetic acid, etc.

[0035] The first initiator includes any one or more of ammonium persulfate, potassium persulfate, hydrogen peroxide and hydrogen peroxide derivatives; the amount used is 1 / 50-1 of the molar mass of the RAFT agent.

[0036] The second initiator includes any one or more of azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, sodium hydrogen persulfate / potassium persulfate redox initiator and sodium persulfate / ammonium persulfate redox initiator. The amount used is 1 / 50-1 of the molar mass of the RAFT agent.

[0037] In step 2, the amount of sodium hydroxide in the sodium hydroxide aqueous solution should be 2-20 times the molar mass of the RAFT agent, and the pH of the system is adjusted to 6-12.

[0038] The highly resilient OCA optical pressure-sensitive adhesive provided by this patent will promote the development of optical display technology. Its performance will improve the quality and life of display devices while maintaining a high level of optical performance. This innovation may also promote the research of OCA materials and create new opportunities for the manufacture of high-quality display devices. The method of preparing pentablock copolymers by RAFT emulsion polymerization may also have a wide range of applications in other material fields, promoting the advancement of materials science.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The present invention utilizes cross-linking of hard segments and soft segments, and the final hard segment is a five-block copolymer of the outer layer, which greatly improves the resilience of the pressure-sensitive adhesive and has excellent strain recovery rate and elongation at break.

[0041] (2) The present invention adopts a reversible addition-fragmentation chain transfer emulsion polymerization controllable design to prepare a five-block copolymer as an OCA optical pressure-sensitive adhesive. This method can accurately control the types and proportions of different segments, and achieve more precise polymer performance regulation. The block copolymer prepared by this method has a high molecular weight and can support the preparation of a high molecular weight five-block copolymer.

[0042] (3) The OCA optical pressure-sensitive adhesive prepared by the pentablock copolymer in the present invention has ultra-high resilience and high elongation at break, which is conducive to the application in high-end display devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a comparison diagram of the five-block copolymer obtained by the present invention with the four-block copolymer and the three-block copolymer.

[0044] Figure 2 It is a comparison diagram of the microphase separation of the pentablock copolymer and the triblock copolymer obtained in the present invention.

[0045] Figure 3 It is the GPC curve chart of the five-block copolymer obtained by the present invention.

[0046] Figure 4 It is a mechanical stretching curve diagram of the OCA optical pressure-sensitive adhesive obtained by the present invention.

[0047] Figure 5 It is a stress relaxation recovery curve diagram of the OCA optical pressure-sensitive adhesive obtained by the present invention. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0049] The raw materials used in the following specific embodiments are all purchased from the market, wherein the dispersion medium is tetrahydrofuran, and the chemical structural formula of the RAFT agent is:

[0050]

[0051] Example 1

[0052] In this embodiment, the poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate-b-styrene) pentablock copolymer is prepared by RAFT reversible addition fragmentation chain transfer emulsion polymerization. The preparation process of OCA optical pressure-sensitive adhesive specifically includes the following steps:

[0053] Step 1, dissolving 1 part by mass of an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent in 15 parts by mass of water, then adding 2 parts by mass of a styrene monomer and stirring until the mixture is uniformly mixed, adding an aqueous potassium sulfate solution (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water) at 90° C., reacting for 2 hours to obtain a styrene homopolymer, wherein the styrene homopolymer is stably dispersed in water in the form of particles to form a latex;

[0054] Step 2, slowly add sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide is dissolved in 10 parts by mass of water), then add 40 parts by mass of isooctyl acrylate, then add 20 parts by mass of water, add 0.02 parts by mass of azobisisobutylimidazoline hydrochloride at 50°C, react for 5 hours in an anaerobic environment, and obtain a poly(styrene-b-isooctyl acrylate) diblock copolymer emulsion.

[0055] Step 3, adding 2 parts by mass of styrene, controlling the reaction temperature at 50° C., and reacting for 5 hours in an oxygen-free environment; obtaining a poly(styrene-b-isooctyl acrylate-b-styrene) triblock copolymer emulsion.

[0056] Step 4, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride and then add 40 parts by mass of isooctyl acrylate, and continue to react for 2 hours in an anaerobic environment to obtain a poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate) tetrablock copolymer latex.

[0057] Step 5, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride and then add 2 parts by mass of styrene, and continue to react for 2 hours in an anaerobic environment to obtain a poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate-b-styrene) pentablock copolymer latex.

[0058] Step 6, after the reaction is completed, pour the polymer latex into 300 parts by weight of diluted hydrochloric acid with a mass fraction of 6 wt%; then wash the precipitated product with distilled water until neutral, dry it in a vacuum oven at 50° C. for 72 hours, and finally obtain a poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate-b-styrene) pentablock copolymer;

[0059] Step 7, dissolving 90 parts by weight of the pentablock copolymer and 10 parts by weight of a tackifying resin in a dispersion medium, coating the mixture in an argon environment to form a film, and drying the mixture to finally obtain an OCA optical adhesive.

[0060] The molecular weight of the polymers was characterized by gel permeation chromatography (GPC) using a Waters 1525-2414-717 instrument with tetrahydrofuran as the eluent and calibration using narrow distribution polystyrene standards.

[0061] The mechanical properties of the polymer were tested by a universal material testing machine (Zwick / Roll Z020). The polymer film prepared in the fourth step was cut into dumbbell-shaped specimens with a standard cutting knife for later use. The test method adopted GB 16421-1996, the tensile rate was 30 mm / min, and the test of each sample was repeated at least three times.

[0062] The stress relaxation recovery performance of the polymer was tested by DMA (TAQ800). The OCA optical pressure-sensitive adhesive film in the fourth step was cut into strips with a width of 5 mm and a length of 25 mm. The OCA optical pressure-sensitive adhesive was stretched for 1 h at a strain of 400%, 600%, 800%, and 1000%, and then maintained at a stress of 0 MPa for 1 h. The recovery data was recorded, and the strain recovery rate was calculated.

[0063] Figure 3The GPC curve data of the five-block copolymer obtained after each reaction is completed. From left to right, the first curve is polystyrene (PSt); the second curve is poly(styrene-b-isooctyl acrylate) (SEHA); the third curve is poly(styrene-b-isooctyl acrylate-b-styrene) (SEHAS); the fourth curve is poly(styrene-b-isooctyl acrylate-b-styrene-isooctyl acrylate) (SEHASEHA); the fifth curve is poly(styrene-b-isooctyl acrylate-b-styrene-isooctyl acrylate-b-styrene) (SEHASEHAS), and the molecular weight of each segment is 1.5W-10W-1.5W-12W-1.5W, respectively.

[0064] Figure 4 ] is the mechanical property curve of the block copolymer. It can be seen from the figure that the polymer has a low modulus of 200.8 KPa, a low stress of 0.79 MPa and a high elongation at break close to 2200%. Figure 5 The strain recovery rate data of OCA optical pressure-sensitive adhesive shows that under 400% tensile strain, the strain recovery rate is 98.7%; under 600% tensile strain, the strain recovery rate is 98.9%; under 800% tensile strain, the strain recovery rate is 98.5%; under 1000% tensile strain, the final deformation rate is only 98.6%.

[0065] Preparation process of poly(styrene-b-isooctyl acrylate-b-styrene) triblock copolymer:

[0066] The first step: 1 part by mass of an amphiphilic macromolecular RAFT agent (amphiphilic macromolecular reversible addition fragmentation chain transfer agent) and 13 parts by mass of water are stirred until completely dissolved, and then 3 parts by mass of styrene are added and then stirred and mixed. The chemical structure of the amphiphilic macromolecular RAFT agent is:

[0067]

[0068] Step 2: Add the above raw materials into a four-necked flask, deoxygenate with nitrogen at room temperature for 0.5h, heat the water bath to 70°C, add an initiator potassium persulfate aqueous solution (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water), and react for 1h. Then slowly add a sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide dissolved in 10 parts by mass of water), then add 80 parts by mass of isooctyl acrylate and 50 parts by mass of water, then add 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, and react for 2h. Finally, add 3 parts by mass of styrene, react for 1.5h to obtain a polymer latex;

[0069] Step 4: After the reaction is completed, the precipitated product is washed with distilled water several times until it is neutral, dried in a vacuum oven at 120°C for 12 hours, and finally white polymer particles are obtained;

[0070] Step 5: Dissolve the polymer in butanone and pour it into a polytetrafluoroethylene watch dish with a diameter of 12 cm to form a film. First, evaporate most of the solvent at room temperature, then place it in a vacuum oven at 130°C to continue drying and annealing to prepare a polymer film with a thickness of about 0.8 to 1 mm.

[0071] Preparation process of poly(styrene-b-isooctyl acrylate-b-styrene-b-isooctyl acrylate) tetrablock copolymer:

[0072] The first step: 1 part by mass of an amphiphilic macromolecular RAFT agent (amphiphilic macromolecular reversible addition fragmentation chain transfer agent) and 13 parts by mass of water are stirred until completely dissolved, and then 3 parts by mass of styrene are added and then stirred and mixed. The chemical structure of the amphiphilic macromolecular RAFT agent is:

[0073]

[0074] Step 2: Add the above raw materials into a four-necked flask, deoxygenate with nitrogen at room temperature for 0.5h, heat the water bath to 70°C, add an initiator potassium persulfate aqueous solution (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water), and react for 1h. Then slowly add a sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide dissolved in 10 parts by mass of water), then add 70 parts by mass of isooctyl acrylate and 50 parts by mass of water, then add 0.02 parts by mass of azobisisobutylimidazoline hydrochloride, and react for 2h. Then add 3 parts by mass of styrene, react for 1.5h, and obtain a polymer latex. Finally, add 10 parts by mass of isooctyl acrylate and 30 parts by mass of water. ;

[0075] Step 4: After the reaction is completed, the precipitated product is washed with distilled water several times until it is neutral, dried in a vacuum oven at 120°C for 12 hours, and finally white polymer particles are obtained;

[0076] Step 5: Dissolve the polymer in butanone and pour it into a polytetrafluoroethylene watch dish with a diameter of 12 cm to form a film. First, evaporate most of the solvent at room temperature, then place it in a vacuum oven at 130°C to continue drying and annealing to prepare a polymer film with a thickness of about 0.8 to 1 mm.

[0077] Table 1 shows the comparison of tensile mechanical properties of the pentablock copolymer with triblock copolymer and tetrablock copolymer having the same hard segment and soft segment content. It can be seen that the interaction between chains of the pentablock copolymer is stronger and can withstand a greater tensile strength at break.

[0078] Table 1 Comparison of properties of pentablock copolymers, triblock copolymers and tetrablock copolymers in Example 1

[0079] sample Modulus / kPa Stress / MPa Elongation at break / % Example 1 (pentablock copolymer) 200.8 0.79 2200 Triblock copolymer 181.2 0.47 1200 Tetrablock copolymer 162.4 0.64 1000

[0080] Example 2

[0081] In this embodiment, the poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) pentablock copolymer is prepared by RAFT reversible addition fragmentation chain transfer emulsion polymerization. The preparation process of OCA optical pressure-sensitive adhesive specifically includes the following steps:

[0082] Step 1, dissolving 1 part by mass of an amphiphilic macromolecular reversible addition-fragmentation chain transfer reagent in 15 parts by mass of water, then adding 2 parts by mass of a styrene monomer and stirring until the mixture is uniformly mixed, adding an aqueous potassium sulfate solution (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water) at 40° C., and reacting for 3 hours to obtain a styrene homopolymer, wherein the styrene homopolymer is stably dispersed in water in the form of particles to form a latex;

[0083] Step 2, slowly add a sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide is dissolved in 10 parts by mass of water), then add a mixture of 30 parts by mass of isooctyl acrylate and 10 parts by mass of n-butyl acrylate, then add 20 parts by mass of water, add 0.02 parts by mass of azobisisobutylimidazoline hydrochloride at 30°C, react for 15 hours in an anaerobic environment, and obtain a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)) diblock copolymer emulsion.

[0084] Step 3, adding 3 parts by mass of styrene, controlling the reaction temperature at 30° C., and reacting for 15 hours in an oxygen-free environment; obtaining a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) triblock copolymer emulsion.

[0085] Step 4, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride, and then add a mixture of 20 parts by mass of isooctyl acrylate and 10 parts by mass of n-butyl acrylate, and continue to react for 15 hours in an anaerobic environment to obtain poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)) tetrablock copolymer latex.

[0086] Step 5, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride and then add 4 parts by mass of styrene, and continue to react for 15 hours in an anaerobic environment to obtain a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) pentablock copolymer latex.

[0087] Step 6, after the reaction is completed, pour the polymer latex into 300 parts by weight of diluted hydrochloric acid with a mass fraction of 6 wt%; then wash the precipitated product with distilled water until neutral, dry it in a vacuum oven at 50° C. and vacuum dry it for 72 hours to finally obtain a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) pentablock copolymer;

[0088] Step 7, dissolving the pentablock copolymer in a dispersion medium, coating it in an argon environment to form a film, and drying it to finally obtain an OCA optical adhesive.

[0089] The molecular weight characterization and mechanical property tests of the polymer in this example are similar to those in Example 1. Figure 5 The strain recovery rate data of OCA optical pressure-sensitive adhesive shows that under 400% tensile strain, the strain recovery rate is 98.3%; under 600% tensile strain, the strain recovery rate is 99.4%; under 800% tensile strain, the strain recovery rate is 99.5%; under 1000% tensile strain, the final deformation rate is only 98.3%.

[0090] The amount of styrene added in step 1, step 3 and step 5 was adjusted, and the preparation process remained unchanged, and the mechanical properties of the obtained pentablock copolymers were compared, as shown in Table 2. It can be seen that with the decrease in the content of styrene hard segment, the modulus of the optical adhesive is reduced, and the elongation at break and the rebound rate are improved, indicating that the reduction of the hard segment content is conducive to the improvement of the rebound elasticity and elongation at break of the optical adhesive.

[0091] Table 2 compares the mechanical properties of different styrene mass fractions

[0092]

[0093] Embodiment 3:

[0094] The poly(styrene-b-isooctyl acrylate-b-styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) pentablock copolymer is prepared by RAFT reversible addition fragmentation chain transfer emulsion polymerization. The preparation process of OCA optical pressure-sensitive adhesive specifically includes the following steps:

[0095] Step 1, dissolving 1 part by mass of an amphiphilic macromolecular reversible addition-fragmentation chain transfer reagent in 15 parts by mass of water, then adding 2 parts by mass of a styrene monomer and stirring until the mixture is uniformly mixed, adding an aqueous potassium sulfate solution (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water) at 90° C., reacting for 1 hour to obtain a styrene homopolymer, wherein the styrene homopolymer is stably dispersed in water in the form of particles to form a latex;

[0096] Step 2, slowly adding a sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide is dissolved in 10 parts by mass of water), then adding 30 parts by mass of isooctyl acrylate, then adding 20 parts by mass of water, adding 0.02 parts by mass of azobisisobutylimidazoline hydrochloride at 60° C., reacting for 2 hours in an anaerobic environment, to obtain a poly(styrene-b-isooctyl acrylate) diblock copolymer emulsion;

[0097] Step 3, adding 3 parts by mass of styrene, controlling the reaction temperature at 60° C., and reacting for 2 hours in an oxygen-free environment; obtaining a poly(styrene-b-isooctyl acrylate-b-styrene) triblock copolymer emulsion.

[0098] Step 4, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride, and then add a mixture of 20 parts by mass of isooctyl acrylate and 10 parts by mass of n-butyl acrylate, and continue to react for 2 hours in an anaerobic environment to obtain a poly(styrene-b-isooctyl acrylate-b-styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)) tetrablock copolymer latex;

[0099] Step 5, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride and then add 4 parts by mass of styrene, and continue to react for 2 hours in an oxygen-free environment to obtain a poly(styrene-b-isooctyl acrylate-b-styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) pentablock copolymer latex;

[0100] Step 6, after the reaction is completed, pour the polymer latex into 300 parts by weight of diluted hydrochloric acid with a mass fraction of 6 wt%; then wash the precipitated product with distilled water until neutral, dry it in a vacuum oven at 50° C. for 72 hours, and finally obtain a poly(styrene-b-isooctyl acrylate-b-styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) pentablock copolymer;

[0101] Step 7, dissolving 80 parts by weight of the pentablock copolymer, 10 parts by weight of the tackifying resin and 10 parts by weight of the antioxidant in a dispersion medium, coating the mixture in an argon environment to form a film, and drying the mixture to finally obtain an OCA optical adhesive.

[0102] The molecular weight characterization and mechanical property tests of the polymer in this example are similar to those in Example 1. Figure 5 The strain recovery rate data of OCA optical pressure-sensitive adhesive shows that under a tensile strain of 400%, the strain recovery rate is 99.0%; under a tensile strain of 600%, the strain recovery rate is 99.2%; under a tensile strain of 800%, the strain recovery rate is 98.6%; under a tensile strain of 1000%, the final deformation rate is only 98.9%.

[0103] Embodiment 4:

[0104] The poly(styrene-b-(isooctyl acrylate-ran-butyl acrylate)-b-styrene-b-isooctyl acrylate-b-styrene) pentablock copolymer is prepared by RAFT reversible addition fragmentation chain transfer emulsion polymerization. The preparation process of OCA optical pressure-sensitive adhesive specifically includes the following steps:

[0105] Step 1, dissolving 1 part by mass of an amphiphilic macromolecular reversible addition-fragmentation chain transfer reagent in 15 parts by mass of water, then adding 2 parts by mass of a styrene monomer and stirring until the mixture is uniformly mixed, adding an aqueous potassium sulfate solution (0.02 parts by mass of potassium persulfate dissolved in 12 parts by mass of water) at 70° C., reacting for 1.5 hours to obtain a styrene homopolymer, wherein the styrene homopolymer is stably dispersed in water in the form of particles to form a latex;

[0106] Step 2, slowly adding a sodium hydroxide aqueous solution (1 part by mass of sodium hydroxide is dissolved in 10 parts by mass of water), then adding 40 parts by mass of isooctyl acrylate and 30 parts by mass of n-butyl acrylate, then adding 70 parts by mass of water, adding 0.02 parts by mass of azobisisobutylimidazoline hydrochloride at 50° C., reacting for 4 hours in an anaerobic environment, and obtaining a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)) diblock copolymer emulsion;

[0107] Step 3, adding 3 parts by mass of styrene, controlling the reaction temperature at 50° C., and reacting in an oxygen-free environment for 4 hours; obtaining a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene) triblock copolymer emulsion.

[0108] Step 4, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride and then add 40 parts by mass of isooctyl acrylate, and continue to react for 2 hours in an anaerobic environment to obtain poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene-b-isooctyl acrylate) tetrablock copolymer latex.

[0109] Step 5, continue to add 0.01 parts by mass of azobisisobutylimidazoline hydrochloride and then add 4 parts by mass of styrene, and continue to react for 2 hours in an anaerobic environment to obtain a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene-b-isooctyl acrylate-b-styrene) pentablock copolymer latex.

[0110] Step 6, after the reaction is completed, pour the polymer latex into 300 parts by weight of dilute hydrochloric acid with a mass fraction of 6 wt%; then wash the precipitated product with distilled water until neutral, dry it in a vacuum oven at 50° C. for 72 hours, and finally obtain a poly(styrene-b-(isooctyl acrylate-ran-n-butyl acrylate)-b-styrene-b-isooctyl acrylate-b-styrene) pentablock copolymer;

[0111] Step 7, dissolving 90 parts by weight of the pentablock copolymer and 10 parts by weight of the antioxidant IRGANOX 1076 in tetrahydrofuran, a dispersion medium, coating to form a film in an argon environment, and drying to finally obtain an OCA optical adhesive.

[0112] The molecular weight characterization and mechanical property tests of the polymer in this example are similar to those in Example 1. Figure 5 The strain recovery rate data of OCA optical pressure-sensitive adhesive shows that under 400% tensile strain, the strain recovery rate is 98.9%; under 600% tensile strain, the strain recovery rate is 98.2%; under 800% tensile strain, the strain recovery rate is 98.6%; under 1000% tensile strain, the final deformation rate is only 99.4%.

[0113] The peel strength of the block polymers prepared in Examples 1-4 was tested by an adhesive shear strength tester (KJ-1066A), and the obtained OCA optical pressure-sensitive adhesive film was cut into strips with a width of 25 mm and a length of about 300 mm. The test method adopted GB / T 2792-2014, and the test of each sample was repeated at least three times. Among them, Example 2 refers to copolymer 1, and the peel strength data are shown in Table 3.

[0114] It can be seen that when the pressure-sensitive adhesive obtained in Example 1 has a film thickness of 25 μm, the peel strength of the OCA optical pressure-sensitive adhesive film is 16.5 N / 25 mm. The peel strength of Example 2 is 8.3 N / 25 mm. The peel strength of the OCA optical pressure-sensitive adhesive film of Example 3 is 15.7 N / 25 mm. The peel strength of the OCA optical pressure-sensitive adhesive film of Example 4 is 7.8 N / 25 mm. The reason is that the addition of the tackifying resin and the increase in the hard segment content can improve the peel strength.

[0115] Table 3 Peel strength of OCA optical pressure-sensitive adhesives prepared in Examples 1-4

[0116] sample Peel strength (N / 25mm) Example 1 16.5 Example 2 8.3 Example 3 15.7 Example 4 7.8

[0117] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. An OCA optical pressure-sensitive adhesive with high resilience and high elongation at break, characterized in that: Based on 100% of the total mass, it includes 70-100% of a five-block copolymer, 0-20% of a tackifying resin and 0-10% of an antioxidant; The general structural formula of the five-block copolymer is M1-b-M2-b-M3-b-M4-b-M5, wherein M1, M2, M3, M4, and M5 are comonomers in the block copolymer, wherein M1, M3, and M5 are selected from hard monomers or a mixture of hard monomers and functional monomers, and their total mass accounts for less than 30% of the comonomers; M2 and M4 are selected from soft monomers or a mixture of soft monomers and functional monomers, and their total mass accounts for more than 70% of the comonomers.

2. The OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 1, characterized in that: The number average molecular weight of the five-block copolymer is 100,000 to 1,000,000 g / mol; the number average molecular weight of the blocks formed by M1, M3 and M5 is 0.5 to 40,000 g / mol; the number average molecular weight of the blocks formed by M2 and M4 is 50,000 to 500,000 g / mol.

3. The OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 1, characterized in that: The hard monomer includes one or more of styrene, methyl acrylate, isobornyl acrylate, cyclohexyl acrylate, methyl methacrylate, acrylamide, acrylonitrile and vinyl acetate, and the glass transition temperature thereof is in the range of 60 to 150° C.; The soft monomer comprises one or more of ethyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, isooctyl acrylate, octyl acrylate, 2-propylheptyl acrylate, isononyl acrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, isooctyl methacrylate, butadiene, isoprene, ethylene-butene and methacrylic acid, and the glass transition temperature ranges from -90 to -30°C; The functional monomers include one or more of methacrylic acid, acrylic acid, itaconic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, ethylenedimethylamine methacrylate, methacrylic acid amine, N-hydroxymethyl acrylamide, glycidyl methacrylate and maleic anhydride.

4. The OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 1, characterized in that: The masses of M1, M2, M3, M4 and M5 are 1-10%, 30%-60%, 1-10%, 30-60% and 1-10% of the total comonomer mass respectively, and the total mass of the comonomers is 100%.

5. The OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 1, characterized in that: When M1, M3, and M5 are selected from a mixture of hard monomers and functional monomers, the functional monomers account for 1-15% of the total monomer mass; When M2 and M4 are selected from a mixture of soft monomers and functional monomers, the functional monomers account for 1-30% of the total monomer mass.

6. The OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 1, characterized in that: The tackifying resin includes one or more of T-801, T-801L, 900L, 901L, TP2019 and 803L; The antioxidant includes any one or more of dialkyl phosphite, triisooctyl phosphite, thiophosphoryl disulfide, antioxidant 1010, antioxidant 168, IRGANOX 1726, IRGANOX 1010, and IRGANOX 1076 of BASF of Germany; The dispersion medium includes any one or more of diethyl ether, methyl tert-butyl ether, tetrahydrofuran, methyl ethyl ketone, ethyl acetate and methyl propionate.

7. The method for preparing the OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 1, characterized in that: Includes steps: Step 1, dissolving the RAFT agent in water, adding the M1 monomer and mixing, then adding the first initiator, and reacting for 1-3 hours to obtain a latex formed by the M1 homopolymer; Step 2, adding sodium hydroxide aqueous solution to the latex of step 1, then adding M2 monomer, water and the second initiator, reacting for 2-15 hours in an anaerobic environment to obtain a M1-b-M2 diblock copolymer emulsion; then sequentially adding M3 monomer, M4 monomer and M5 monomer, adding the second initiator after each addition of new monomers, reacting for 2-15 hours in an anaerobic environment to obtain a M1-b-M2-b-M3-b-M4-b-M5 pentablock copolymer emulsion; Step 3, mixing the pentablock copolymer emulsion with a demulsifier, washing and drying the precipitated product to obtain the pentablock copolymer; Step 4, dissolving the pentablock copolymer, tackifying resin and antioxidant in a dispersion medium, coating to form a film in an inert gas environment, and drying to obtain the OCA optical pressure-sensitive adhesive.

8. According to the method for preparing an OCA optical pressure-sensitive adhesive with high resilience and high elongation at break as claimed in claim 7, the reaction temperature in step 1 is 40-90°C; the reaction temperature in step 2 is 30-60°C; the demulsification temperature in step 3 is 30-60°C; and the demulsification time is more than 0.1h.

9. The method for preparing an OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 7, wherein the chemical structural formula of the RAFT agent is: R-(M n1 -bN n2 )-X; where R is isopropanoyl, acetyl, 2-cyanoacetyl or 2-aminoacetyl; M n1 In the formula, M is a methacrylic acid monomer or an acrylic acid monomer unit, n1 is the average polymerization degree of M, and n1 ranges from 10 to 30; N n2 wherein N is a styrene monomer, n-butyl acrylate monomer, methyl acrylate, isooctyl acrylate or methyl methacrylate monomer unit, n2 is the average degree of polymerization of N, and n2 ranges from 1 to 8; the X group is an alkyl dithioester group or an alkyl trithioester group, and the mass of the RAFT agent added is 0.2% to 1.0% of the total mass of all monomers; The demulsifier includes any one or more of HCl solution, H2SO4 solution, HNO3 solution, HBr acetic acid, lactic acid, formic acid, and acetic acid.

10. The method for preparing an OCA optical pressure-sensitive adhesive with high resilience and high elongation at break according to claim 7, wherein the first initiator comprises any one or more of ammonium persulfate, potassium persulfate, hydrogen peroxide and hydrogen peroxide derivatives; the amount used is 1 / 50-1 of the molar mass of the RAFT agent; The second initiator includes any one or more of azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, sodium hydrogen persulfate / potassium persulfate redox initiator and sodium persulfate / ammonium persulfate redox initiator, and the amount used is 1 / 50-1 of the molar mass of the RAFT agent.

Citation Information

Patent Citations

  • UV semi-curing OCA (optical clear adhesive) and use thereof

    CN108977160A